Feasibility of Solar Updraft Towers as Photocatalytic Reactors for Removal of Atmospheric Methane–The Role of Catalysts and Rate Limiting Steps - Huang, Yanfang; Shao, Yimin; Bai, Yang; Yuan, Qingchun; Ming, Tingzhen; Davies, Philip; Lu, Xiaohua; de Richter, Renaud; Li, Wei (Frontiers in Chemistry, 2021)
An increasing number of research highlight the fact that in order to have some chances to stay below the 2°C global average warming target fixed at the Paris agreement on the climate, greenhouse gas removal from atmosphere will be absolutely necessary in the coming decades. Methane is the second most harmful greenhouse gas accounting for 25% of radiative forcing and its concentration is increasing rapidly. Our previous study reviewed the potential of heterogeneous photocatalytic reactions to destroy a large quantity of methane from air. It was proposed to incorporating photocatalysis with solar updraft Towers (SUT) to remove methane from the air at a planetary scale. In this study, we present a review and deep analysis by calculating the potential of methane removal in relation to the dimensions and configuration of SUT using different photocatalysts. The analysis shows that the methane removal rate increases with the SUT dimensions and can be enhanced by changing the configuration design. More importantly, the low methane removal rate on conventional TiO2 photocatalyst can be significantly improved to, for example,42.5% on a more effective Ag-doped ZnO photocatalyst in a 200 MW SUT while the photocatalytic reaction is the rate limiting step. The factors that may further affect the removal of methane, such as more efficient photocatalysts, night operation and reaction zone are discussed as possible solutions to further improve the system.